Proceedings of the 7th International Conference on Intelligent Technologies for Interactive Entertainment 2015
DOI: 10.4108/icst.intetain.2015.259625
|View full text |Cite
|
Sign up to set email alerts
|

How Does It Feel Like? An Exploratory Study of a Prototype System to Convey Emotion through Haptic Wearable Devices

Abstract: Abstract-This paper reports on the design and implementation of a portable, hands-free, wearable haptic device that maps the emotions evoked by the music in a movie into vibrations, with the aim that hearing-impaired audience can get a sense of the emotional content carried by the music in specific movie scenes, and therefore feel (hear) the music through the sense of touch. A study of the use of the technology is reported which found that high arousal and high valence were reliably conveyed through haptic pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 12 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…Table A.4 reports the results from the Wilcoxon Signed-Ranks Test for both the valence and the arousal dimensions, describing pairs of patterns which resulted significantly different. Visual representations of the arousal and valence average ratings, and confusion matrix for the pairs of patterns which reported significance differences in the Wilcoxon Signed-Ranks test are available in Mazzoni and Bryan-Kinns [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table A.4 reports the results from the Wilcoxon Signed-Ranks Test for both the valence and the arousal dimensions, describing pairs of patterns which resulted significantly different. Visual representations of the arousal and valence average ratings, and confusion matrix for the pairs of patterns which reported significance differences in the Wilcoxon Signed-Ranks test are available in Mazzoni and Bryan-Kinns [32].…”
Section: Resultsmentioning
confidence: 99%
“…Actuators intensity and frequency is controlled through manipulation of the PWM signal as in Frid et al [34]. For further discussion of the significance of the results see [32]. This user study informed the next step of this work, in which participants sensed haptic patterns while watching movie clips, for a cross-modal experience.…”
Section: Discussionmentioning
confidence: 97%
“…A haptic device employs technology that delivers haptic feedback, i.e., potentially both kinaesthetic and tactile feedback. Haptics have become ubiquitous today and are commonly found in mobile phones and tablet devices (Mazzoni and Bryan-Kinns 2015a).…”
Section: Replicating Tactile Feedback With Haptic Music Playersmentioning
confidence: 99%
“…They found that users were able to both recognize and communicate emotions beyond chance through the haptic joystick. In a study by Mazzoni and Bryan-Kinns (2015), the design and evaluation of a haptic glove for mapping emotions evoked by music were found to reliably convey pleasure and arousal. Bonnet et al (2011) found that facial expression emotion recognition was improved when utilizing a "visio-haptic" platform for virtual avatars and a haptic arm joystick.…”
Section: Stimuli and Perceptionmentioning
confidence: 99%